Does pyogenic liver abscess increase the risk of delayed-onset primary liver cancer?: Evidence from a nationwide cohort study - Chu, Chia-Sheng (Medicine (Baltimore), 2017)
Delayed-onset primary liver cancer (PLC) including hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC) in patients with pyogenic liver abscess (PLA) is not common. The relationship between PLA and delayed-onset PLC is unclear. We investigated the association in a nationwide cohort study. From Taiwan National Health Insurance claims data, a cohort of 17,531 patients with PLA was generated after excluding patients with a history of cancer (n = 2034) and those diagnosed with PLC (n = 572) and other cancers (n = 627) within 1 year of a diagnosis of PLA. An age-, sex-, index year-, and diabetes mellitus (DM)-matched control cohort of 70,124 persons without PLA was selected from the same dataset. Both cohorts were followed up until the end of 2011. The risk of PLC was estimated for both cohorts. The incidence of PLC was nearly 2-fold greater in the PLA group than in the control cohort (29.3 per 10,000 person-years vs. 16.2 per 10,000 person-years). The incidences of HCC and ICC were 1.5- (22.1 per 10,000 person-years vs. 15.0 per 10,000 person-years) and 11-fold greater (6.73 per 10,000 person-years vs. 0.62 per 10,000 person-years), respectively, in the PLA group than in the control cohort. The PLA cohort also had high risks of PLC (adjusted hazard ratio [aHR] = 1.56; 95% confidence interval [CI] = 1.35–1.81), HCC (aHR = 1.34; 95% CI = 1.15–1.57), and ICC (aHR = 6.94; 95% CI = 4.23–11.57). In conclusion, in this nationwide cohort study, PLA increased the risk of delayed-onset PLC.